Climate change and disaster management - O'Brien, Geoff...[et al.] (2006)
Opines that since climate change is a source of multiple hazards that threaten long-term development actions by the international community, the concensus and planning approaches that have linked development and disaster should extend to climate change. Shows that this extension has not yet taken place and argues that it is urgent that it does occur.